Evaluación biológica en la eficiencia en la degradación de celulosa sustancias lignocelulósicas en compostaje (2024)
The objective of this study is to evaluate the biological efficiency in the degradation of cellulose and lignocellulosic substances during composting, in order to improve the sustainable management of organic waste. The methodology included the identification and characterization of microorganisms from different natural sources, the evaluation of their capacity to degrade these substrates under optimal laboratory culture conditions and the analysis of the impact of biological pretreatment with unicellular microorganisms on composting efficiency.